Retaining Wall Design in Addressing the Waterlogging Problem in Tambaklorok - Melinda Dwi Rahmawati; Ahmad Rifa'i; Fajar Dwi Satriaji (CIVED, 2025)
North Semarang is a densely populated area. Several villages are located not only on the North Coast of Java but also at the mouth of the Semarang River, and these villages are often hit by inundation floods. One of the causes of flooding in Tambak Lorok, Semarang is land subsidence and high tide or ROB. To handle the inundation that occurs, a study of the calculation of the retaining wall structure to hold back the inundation so that it does not enter the Old GIS Switchyard of Tambak Lorok Substation Semarang. The retaining wall planned with a total height of 1.8 m and a bottom width of 0.85 m is stable to the bearing capacity of the soil and safe against overturning and sliding. The bearing capacity of 18 drill pile foundation points with a diameter of 40 cm at a depth of 14 meters is sufficient to withstand the retaining wall and the load above it (350,424 tons > 264,384 tons).